MYSTERIES OF BLACK HOLES AND DARK MATTER - Labrecque, Ellen (North Mankato, Minnesota : Pebble, a Capstone imprint, 2021)
"What is a black hole? What is dark matter and what is it made of? How do scientists discover black holes and dark matter if they can't be seen? What do scientists know about these mysterious parts of the universe and what do they still hope to find out? Budding astronomers will learn the answers to these questions and more!"--
So much still to learn.
Includes bibliographical references (page 31) and index.
Keywords: Black holes (Astronomy) -- Juvenile literature; Dark matter (Astronomy) -- Juvenile literature